The influence of career commitment and workload on academics’ job satisfaction: the moderating role of a supportive environment - Janib, Jamali; Mohd Rasdi, Roziah; Zaremohzzabieh, Zeinab (Society for Research and Knowledge Management, 2022)
This paper serves to study the influences of career commitment and workload on job satisfaction among academics in higher education. We investigated whether a supportive environment is a significant moderator between workload and job satisfaction. For this cross-sectional study, the stratified random sampling method yielded 191 academics from five research universities in Malaysia. Partial least squares-structural equation modeling (PLS-SEM) showed that high levels of career commitment correspond with high levels of satisfaction at work of academics. Also, a greater workload diminishes job satisfaction among academics. The analysis of the interaction-moderation dynamics showed that a supportive environment reduces workload effects on academics’ job satisfaction. This study contributes to confirming the important roles of career commitment and workload in predicting job satisfaction. It also expands literature on the buffering role of a supportive environment in the interaction between workload and job satisfaction among academics.